Acute Interstitial Nephritis in a Patient with Non-Small Cell Lung Cancer under Immunotherapy with Nivolumab. (15th January 2019) - Georgianos, Panagiotis I.; Vaios, Vasilios; Leontaridou, Eleni; Karayannopoulou, Georgia; Koletsa, Triantafyllia; Sioulis, Athanasios; Balaskas, Elias V.; Zebekakis, Pantelis E.
Abstract : Immune-checkpoint-inhibitors (ICPIs) represent a novel class of immunotherapy against several malignancies. These agents are associated with several "immune-mediated" adverse effects, but the reported renal toxicity of ICPIs is less well defined. We present the case of a 60-year-old man with a history of non-small cell lung cancer, who developed acute kidney injury (AKI) approximately 3.5 months after initiation of immunotherapy with nivolumab. Urinalysis revealed sterile pyuria, without microscopic hematuria or proteinuria. Immunological examination was negative. A renal biopsy showed severe interstitial inflammatory infiltration of T-cells, monocytes, and eosinophils without interstitial granulomas and normal appearance of glomeruli, indicating acute interstitial nephritis (AIN) as the cause of AKI. After a short-term course of corticosteroids and permanent nivolumab discontinuation, partial recovery of renal function was noted. AIN is a rare adverse effect of ICPIs that mandates the close monitoring of renal function in patients under immunotherapy with these agents.